Factors associated with self-reported HIV testing in the Dominican Republic. (May 2020) - Haider, Mohammad R; Brown, Monique J; Karim, Sabrina; Siddiqi, Khairul A; Olatosi, Bankole; Li, Xiaoming
Human immunodeficiency virus (HIV) testing is important for controlling the epidemic in low- and middle-income countries such as the Dominican Republic (DR) – a country in the Caribbean. This study aimed to examine factors associated with HIV testing in the DR. The study used HIV test data in the 2013 DR Demographic and Health Survey. HIV data were collected from 18, 614 individuals aged 15–59 years. Wealth status, HIV-related stigma, and knowledge scales were constructed using factor analysis. Survey-weighted logistic regression was used to identify correlates of HIV testing in the DR. Results show that almost two-thirds (62.4%) of the participants reported ever having an HIV test. In the multivariable analysis, older age, higher education, female gender, richest wealth status, health insurance, married, higher HIV-knowledge, and lower HIV-related stigma increased the likelihood of getting an HIV test in the DR. People living in Norte/Cibao, which had a higher HIV prevalence, had a lower chance of having an HIV test than people living in the Este/Sureste region. Although HIV testing has increased in recent times, it is not yet satisfactory in the DR. Specific interventions building HIV awareness targeting specific sub-populations and regions will increase knowledge on HIV and reduce HIV-related stigma, and may increase HIV testing.